Context value updating and multidimensional neuronal encoding in the retrosplenial cortex - Weilun Sun; Ilseob Choi; Stoyan Stoyanov; Oleg Senkov; Evgeni Ponimaskin; York Winter; Janelle M. P. Pakan; Alexander Dityatev (Nature Communications, 2021)
Goal-directed behaviors require the brain to integrate information across many task-related dimensions. Here, the authors use a virtual context discrimination paradigm in mice to demonstrate the capacity for neurons in the retrosplenial cortex to exhibit multidimensional encoding across learning.